Research Landscape of Artificial Intelligence and e-Learning: A Bibliometric Research - Jia, Kan; Wang, Penghui; Li, Yang; Chen, Zezhou; Jiang, Xinyue; Lin, Chien-Liang; Chin, Tachia (Frontiers in Psychology, 2022)
As research on artificial intelligence is increasingly concerned, the application of artificial intelligence in online learning grows a new important issue and method in recent years. Over the past few decades, the importance of online learning has also been concerned in many fields, such as technological education, STEAM, AR/VR apps, online learning, etc. Of course, in order to effectively explore research trends in this area, the current state of online learning should be understood surely. Systematic bibliometric analysis can address this problem by providing information on publishing trends and their relevance on various topics. In this study, the literature application of artificial intelligence combined with online learning from 2010 to 2021 was analyzed, 64 articles were collected to analyze the most productive countries, universities, authors, journals and publications in the field of artificial intelligence combined with online learning using VOSviewer through WOS data collection, and the mapping of co-citation and co-occurrence (CC) was explored through the analysis of knowledge map. The main objective to this study is to provide an overview of trends and pathways in artificial intelligence and online learning, so as to help researchers understand global trends and future research directions.